2023
DOI: 10.4081/jlimnol.2023.2129
|View full text |Cite
|
Sign up to set email alerts
|

Survival and swimming performance of a small-sized Cypriniformes (<em>Telestes muticellus</em>) tagged with passive integrated transponders

Abstract: Italian riffle dace (Telestes muticellus, Bonaparte 1837) is a small-bodied Leuciscidae native to the Italian Peninsula, of which little is known about the ecology and individual movements in nature. Passive Integrated Transponder (PIT) telemetry is used to track fish movements and behaviour. The basic assumption is that the PIT-tagged organism's performances do not differ considerably from their natural behaviour. Here we present the first evaluation of potential tagging effects in the genus Telestes. The sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…We anticipated that trapping might have caused some problems for the fish as the fyke net trap was situated in fast-flowing water, up to 1 m s À1 , without any refuge from the current. Although, more subtle tagging effects cannot be excluded (Schiavon et al, 2023), the results from our procedural controls using dummy tags and untagged fish indicated that mortality due to tagging and/or trapping was low and occurred within 24 h. Our fish were held at least 30 h after tagging and only fish that looked healthy were released. As an extra precaution to avoid overestimating mortality, fish that did not initiate downstream migration within 24 h after release were excluded from the study.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipated that trapping might have caused some problems for the fish as the fyke net trap was situated in fast-flowing water, up to 1 m s À1 , without any refuge from the current. Although, more subtle tagging effects cannot be excluded (Schiavon et al, 2023), the results from our procedural controls using dummy tags and untagged fish indicated that mortality due to tagging and/or trapping was low and occurred within 24 h. Our fish were held at least 30 h after tagging and only fish that looked healthy were released. As an extra precaution to avoid overestimating mortality, fish that did not initiate downstream migration within 24 h after release were excluded from the study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the extensive construction of fish passages to mitigate freshwater migratory fish decline, the efficacy of these structures is debated, as numerous structures suffer from low passage efficiency 63 , 64 . An effective exploratory behaviour is crucial for fish to search and locate entrances of fishways at river barriers 63 65 , and while extensive research has focused on enhancing the attractiveness of such entrances for individual fish 64 , 66 , 67 , very little is known about the case of shoaling fish 17 , 68 . Emerging experimental evidence, such as studies on gudgeons ( Gobio gobio ) 69 and barbels ( Barbus barbus ) 70 , suggests that aggregation can lead to increased passage efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…A subsample of the Telestes muticellus greater than 6.0 cm, corresponding to a size range of fish older than 1 yr, was tagged with Passive Integrated Transponders (PIT tags; Oregon, USA; 12 Â 2.1 mm; 0.10 g). High survival and tag retention rates were reported for this species (Schiavon et al, 2023). Before tagging, fish were anaesthetised with clove oil (Aromlabs, USA; approximately 0.2 mL clove oil per litre of water).…”
Section: Pit Taggingmentioning
confidence: 99%
“…Before tagging, fish were anaesthetised with clove oil (Aromlabs, USA; approximately 0.2 mL clove oil per litre of water). An incision of 2-4 mm was made on the ventral side of the fish, slightly offset from the centre and frontal to the pelvic fins, before the tag was inserted and pushed forward in the abdomen (Nyqvist et al, 2022;Schiavon et al, 2023). Once the fish had been tagged, they were measured for fork length and weight and allowed to recover in tanks filled with river water.…”
Section: Pit Taggingmentioning
confidence: 99%